Strategi Pengembangan Pariwisata Dalam Mengoptimalkan Pendapatan Asli Daerah Di Dinas Kebudayaan dan Pariwisata Kota Surakarta - Partiwi, Widya; Winarti; Suranto, Joko (Solidaritas, 2024)
The Surakarta City Culture and Tourism Office is a government body which has the taskof formulating policies, carrying out government affairs and public services, developingand implementing as well as monitoring, evaluating and reporting all matters relatingto culture, traditional arts, history, cultural heritage, museums, tourism destinations,tourism marketing, creative economy development through the use and protection ofintellectual property rights, and development of tourism and creative economy resources.The city of Surakarta or the city of Solo, known by its slogan as "The Spirit of Java", is acity that has everything to attract tourists. The city of Surakarta has various types oftourism which attract visits from domestic and foreign tourists, so that the SurakartaCity government is able to utilize the tourism sector to support the economy in the Cityof Surakarta. So this sector is expected to have a significant contribution to the RegionalOriginal Income in the City of Surakarta. This research aims to analyze and describetourism development strategies in optimizing local revenue at the Surakarta City Cultureand Tourism Office. The research method used is descriptive qualitative. Data collectiontechniques in this research were carried out through observation, interviews anddocumentation. The data analysis techniques used are data collection, data condensation,data presentation and drawing conclusions. The results of this research indicate that thetourism development strategy at the Surakarta City Culture and Tourism Office has beenquite successful in increasing income from the tourism sector so that it is able to increaselocal original income in Solo City. This can be seen from the nine indicators found byNawawi (2000: 153), namely: Proactivity, Anticipation, Strengths, Weaknesses,Opportunities and Obstacles, Resource Utilization, Control and Service Standards.These nine indicators have been implemented well. Based on the explanation above, theresearcher provides recommendations to the Surakarta City Culture and Tourism Officeto be able to maintain the indicators that have been implemented well.Keywords: Strategy, Development, Tourism, Culture and Tourism Service.